Prosperity-Preaching in West-Africa: An Evaluation of a Contemporary Ideology from a New Testament Prospective - Kahl, Werner (Ghana bulletin of theology, 2007)
Prosperity preaching is a powerful trend in Pentecostalism and it is also an issue in West-Africa.